Calculation of the available transfer capability of trading channels based on power network congestion forecasting - Wei, Congying; Jia, Longwen; Wang, Xiongwei; Cai, Yu; Huang, Ying; Huang, Yanbo; Liao, Siyang (Frontiers in Energy Research, 2024)
Against the backdrop of increasing renewable energy penetration, frequent power network congestion has become a key issue limiting the available transfer capability of trading channels. In order to avoid power network congestion while improving the overall utilization of trading channels, we propose a method for calculating the available transfer capability of a trading channel based on power network congestion forecasting. First, this study uses a histogram-based gradient tree boosting (HGTB) model to forecast the severity and probability of power network congestion, which enables power system operators to determine the specific circumstances of congestion occurrence. Second, we analyze the sensitivity of the power trading network and generating units to transmission lines, aiming to calculate the available transfer capability of the trading channel on the basis of taking into account the control of transmission line congestion and the balance of supply and demand in the power market. Finally, the validity of the validation methodology is verified based on a case study of the power system in central China.